A survey on ways to improve on the involvement of the locals in the 3D job sector / Nadia Izzatul Akmal Mohamad Isa and Ahmad Arzlee Hassan - Mohamad Isa, Nadia Izzatul Akmal; Hassan, Ahmad Arzlee (2018)
Construction industry has not only been one of the major sources of income in Malaysian economy, but also a platform for employment opportunities to the locals. 3D, an acronym for Dirty, Dangerous and Difficult is very much related to the construction industry. Nowadays, locals are reluctant to be involved in construction industry despite the high demands for job opportunities which lead to the recent import of 1.5 million Bangladeshi to fulfill the job vacancies in various 3D sectors. This research aims to gain a better understanding on how to improve the involvement of locals in 3D job sectors. The research focuses on the construction industry players within the Selangor area through a survey and reviews on various past researches. Although there are some known reasons for employing foreign workers such as low wages, willingness to engage in difficulties etc., however, there are some identified socio-economical issues arising from this arrangement. Multiple initiatives are identified to be the key programme in promoting this professionalism into something that would attract locals. Despite numerous efforts, they are still lack of interest from fastidious youth.